Three‐dimensional ambient noise tomography across the Taiwan Strait: The structure of a magma‐poor rifted margin. Issue 8 (4th August 2016) - Chen, Kai‐Xun; Kuo‐Chen, Hao; Brown, Dennis; Li, Qiusheng; Ye, Zhuo; Liang, Wen‐Tzong; Wang, Chien‐Ying; Yao, Huajian
Abstract: Rifting along southeastern Eurasia in the Late Cenozoic led to the formation of a magma‐poor rifted margin facing the South China Sea to the southeast and the Philippine Sea to the east. Further rifting along the outer part of the margin during the middle to late Miocene was accompanied by an extensive episode of intraplate flood volcanism that formed the Penghu Archipelago. Previous geophysical studies in the area of the strait have focused primarily on the shallow structures of the rift basins and the depth to the Moho. In this study we present the regional‐scale 3‐D S wave structure of the Taiwan Strait that is derived from a joint Chinese and Taiwanese 3‐D ambient noise tomography study. The S wave model shows a thinning of the crust beneath the rift basins where, locally, thin high‐velocity layers suggest the presence of intrusive bodies. The rift basin and the foreland basin along the west coast of Taiwan are imaged as low‐velocity zones with thicknesses between 5 and 10 km and extending eastward beneath the Taiwan mountain belt. In the upper 10 km of the crust, the basaltic rocks of the Penghu Archipelago are imaged as a high‐velocity zone that, with depth, becomes a relatively low‐velocity zone. We interpret this low‐velocity zone in the lower crust and upper mantle beneath the Penghu Archipelago to image a thermal anomaly related to the still cooling magma feeding system and the melt reservoir area that fed the flood basalts at the surface. Key Points: The rifted basins and thinning crust were observed in the Taiwan Strait A low‐velocity zone beneath the Penghu Archipelago was imaged